Study of Completeness and Utilization of Biology Laboratories as Supporting Biology Learning Activities of State Madrasah Aliyah (MAN) in Sleman Regency - Widianti, Imas; Sulistiyawati (Proceeding International Conference on Science and Engineering, 2021)
Abstract: The laboratory is one of the learning infrastructure that can be used to conduct practicum, research, and to improve skills in conducting scientific experiments. This study aims to determine the level of completeness and usefulness of biological laboratory equipment, as well as to determine the intensity of the use of biological laboratories in supporting biology learning in State Madrasah Aliyah throughout Sleman Regency. The sample used, namely 4 MAN includes 103 students of class XI IPA, 3 Heads of Laboratory and 4 Biology teachers. This research is a survey research with a quantitative descriptive approach. Data collection techniques were carried out using observation sheets, questionnaires, and interview sheets. Based on the results of the data analysis, the research showed that the level of completeness of laboratory equipment in MAN in Sleman Regency was 58.5%, while for laboratory conditions the percentage was 96.4%. As well as the level of usefulness of the biology laboratory in supporting learning activities, the result was 78.8%. The intensity of using biological laboratories in MAN in Sleman Regency obtained results with a percentage of 56, 2%. Based on these results, the biology laboratory needs further attention so that it can be improved again so that learning can be achieved optimally.